Salt stress induced effects on biochemical parameters in etiolated maize leaf segments during greening - Meeta Jain* and Jayesh Vaishnav (African Journal of Biological Sciences, 2019)
Treatment of etiolated maize leaf segments with 0-300 mM NaCl during greening decreased the osmotic potential of leaf sap significantly. Na+ content of the leaf tissue increased significantly on supplying different concentrations of salt. Relative water content of the leaf tissue was marginally affected by the supply of NaCl. Total protein and RNA content of the maize leaf segments gradually increased when treated with lower concentrations of NaCl and subsequently decreased at higher concentrations. Decrease in DNA content was noted with increasing salt treatment in a concentration dependent manner. SDS-PAGE analysis of salt treated maize leaf tissue revealed appearance of one protein band (approx. 73 kD) in samples incubated with ≥50 mM NaCl compared to control. Protein identification performed with the Mascot search engine in NCBI database indicated extensive homology of this protein with chloroplast heat shock protein 70 of Cenchrus americanus (Protein score: 295), hypothetical proteins SELMODRAFT_267815 of Selaginella moellendorffii (Protein score: 125), VITISV_000728 of Vitis vinifera (Protein score: 118) and SELMODRAFT_230659 of Selaginella moellendorffii (Protein score: 51). The results revealed that the dark grown maize leaf segments exhibit high degree of stress due to NaCl treatment, which affects the biochemical parameters governing the metabolic activities of the leaf tissue. Further, the stress induced proteins are being synthesized in leaf tissue in response to salt stress.
Keywords: Salt stress, Maize leaf, Protein, NaCl.